Influência do estresse oxidativo sobre as características espermáticas no sêmen de garanhões - Farrás, Marcel Cavalcanti [UNESP] (2015)
A significant number of stallions do not respond in a satisfactory way to the cryopreservation process and that there are many factors involved. In order to elucidate the reasons why some animals have superior results in the spermatic cryopreservation processes, two experiments were conducted. In experiment I, the goal was to evaluate the action of oxidative stress and the consequences in the semen of stallions that were resistant and susceptible to the spermatic freezing process. The influence of the racial factor to the spermatic freezing process was also verified. In experiment II, the goal was to evaluate the influence of the seminal plasma presence on spermatic resistance in cooled semen of stallions considered as bad and good coolers. To evaluate seminal samples, computer analysis of the spermatic cinetic was done (CASA, Thorne Research - HTM IVOS), oxidative stress levels were assessed by thiobarbituric acid-reactive substances (TBARS), sperm DNA fragmentation (HALOMAX) and analysis of the translocation of membrane phospholipids, activated caspase indices and quantification of ROS with flow cytometry were done. In experiment I, there was no influence of the breed factor in relation to the sperm quality of the analyses that were done. Furthermore, the bad freezers stallions, that showed the most loss of seminal quality after spermatic freezing, presented higher rates of oxidative stress and spermatic DNA fragmentation. In experiment II, the stallions that were considered sensitive showed improvement of the sperm quality as the SP was removed. Furthermore, in the good coolers we observed the preservation of sperm quality in the presence of SP and a quality decrease in the samples without the SP. Additionally, we also observed the importance of the test challenge for the evaluation of the sperm analysis, because when submitted to stressful situations, the differences were evident. Keywords: Semen, cryopreservation, oxidative stress...